Docere, delectare et movere. Teacher vision and student prism in the design and implementation of microsites with musical artistic contents (Foro de Educacion, 2017)
In studies of Degree in Early Childhood Education, arts education they have great importance for the competence development of students. So, for its globalization and inclusive it becomes the main axis for the construction of knowledge from other areas. On its behalf, ICT is an essential tool that amplifies the creative essence that provides arts education (Gértrudix & Gértrudix, 2011). In this context, it presents an experience made during the first quarter of 2015-2016 course with students from Degree in Early Childhood Education of Faculty of Education of Toledo (UCLM). We have sought to analyze these Microsites making by students as evidence of learning and to know their teaching skills through classroom implementation of these microsites as proof of their functionality didactic. From a mixed methodology research, it has use the following tools as analysis: a) a documentary analysis of the content and structure of the Microsites created by students b) a SWOT analysis of the educational intervention carried out by students in the childhood classroom and c) a questionnaire to determine the type of ICT tools used in the creation of digital music contents. From the results obtained a clear positive trend among students to the artistic elements emerges, and specially musicals. Thanks to its constant participation and involvement in the whole process of developing the content, students have achieved a remarkable level of competence in instrumental, interpersonal and systemic skills.